Laccadive, Minicoy and Amindivi Islands Approach Papers on the Five Year Plan - Planning Commission (Planning Commission)
Laccadive, Minicoy and Amindivi Islands did not derive benefits under the First Five Year Plan. An attempt was made only in the middle of the Second Five Year Flan to implement an integrated short Plan for the islands. Achievements since then have been remarkable in the field of Education, Fisheries, Agriculture and Works programmes including Harbour Works. According to 1971 Census, population has increased from year 1901- 1971 by 129.15 per cent.
Laccadive, Minicoy and Amindivi Islands